Gene-Xpert: diagnosis of pulmonary tuberculosis in a sputum smear negative patient - Pandey, O; Paudyal, B; Basnyat, B (Nepal Health Research Council, 2019)
This case report has tried to highlight the ease and benefit of Gene-Xpert testing in difficult to diagnose patient with sputum smear negative pulmonary tuberculosis. Early treatment of tuberculosis is usually delayed by lack of rapid and accurate diagnostic modalities, especially in resource-limited settings like ours. Gene-Xpert is a rapid test based on real time PCR assay and molecular technology for the detection of Mycobacterium tuberculosis. It is highly sensitive tool and enables simultaneous detection of rifampicin resistance within short period of time i,e. <2hrs. It has distinct advantage of providing same-day diagnosis which could potentially limit loss to follow up during diagnostic evaluation of smear negative tuberculosis patients. Keywords: Gene-Xpert; pulmonary tuberculosis; sputum microscopy.